HPV vaccine uptake in men who have sex with men in Scotland. Issue 37 (3rd September 2019) - Pollock, K.G.; Wallace, L.A.; Wrigglesworth, S.; McMaster, D.; Steedman, N.
Abstract: Human papillomavirus (HPV) vaccines are currently utilised globally in national immunisation programmes. In July 2017, a national HPV vaccine programme for men who have sex with men (MSM) was initiated across Scotland with vaccine being offered in the sexual health clinic setting. During the first year of this targeted vaccination programme, there were 5905 individuals who received at least one dose of HPV vaccine, representing 63.7% of eligible MSM attendees in this period. Vaccine uptake was relatively stable across all age groups (range 49.8–55.5%). The vaccination programme appears to have dovetailed well with pre-existing sexual health services and appears to be popular with MSM attending the service. The MSM HPV vaccine programme is a robust adjunct to the national girls programme but gender-neutral immunisation will reduce stigma and inequality in HPV-driven disease.